2017
DOI: 10.15605/jafes.032.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome and its Individual Features Across Different (Normal, Overweight, Pre-Obese and Obese) Body Mass Index (BMI) Categories in a Tertiary Hospital in the Philippines

Abstract: Objective. This study aims to determine the prevalence of metabolic syndrome and its individual components across different BMI categories among patients seen at Wellness Center and Obesity and Weight Management Center, St. Luke's Medical Center Quezon City.Methodology. This was a 3-year retrospective study of patients seen at the institution from 2013 to 2016. The patients were divided according to Asia-Pacific BMI categories and presence of metabolic syndrome was determined as defined by NCEP/ATP III-AHA/NHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
0
6
0
Order By: Relevance
“… 17 , 18 For instance, Mata et al observed a noteworthy connection between high BMI and MetS in their retrospective study of the Philippine population. 19 Similarly, Ofer et al reported that a BMI below 30 carries a predictive value of over 90% for excluding MetS. 20 …”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 For instance, Mata et al observed a noteworthy connection between high BMI and MetS in their retrospective study of the Philippine population. 19 Similarly, Ofer et al reported that a BMI below 30 carries a predictive value of over 90% for excluding MetS. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Obesity is less prevalent among the people we studied. Mata A et al observed significant prevalence of metabolic syndrome in people with normal BMI; therefore, screening and diagnosis should not be limited to those with a higher BMI [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) indicators were categorized into five distinct groups: BMI < 18.4—indicative of underweight; BMI ≥ 18.5 and < 24.9—reflecting normal weight; BMI ≥ 25 and < 29.9—indicative of overweight; BMI ≥ 30 and < 34.9—representing obesity of the first degree; and BMI > 35—characterizing obesity of the second degree ( 7 ). The BMI was calculated using a standardized protocol based on the WHO guidelines.…”
Section: Methodsmentioning
confidence: 99%